2016
DOI: 10.18235/0000301
|View full text |Cite
|
Sign up to set email alerts
|

Learning about Oneself: The Effects of Performance Feedback on School Choice

Abstract: work is licensed under a Creative Commons IGO 3.0 AttributionNonCommercial-NoDerivatives (CC-IGO BY-NC-ND 3.0 IGO) license (http://creativecommons.org/licenses/by-nc-nd/3.0/igo/ legalcode) and may be reproduced with attribution to the IDB and for any non-commercial purpose, as provided below. No derivative work is allowed.Any dispute related to the use of the works of the IDB that cannot be settled amicably shall be submitted to arbitration pursuant to the UNCITRAL rules. The use of the IDB's name for any purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…We note that the largest effects were among new students who were likely to be less informed about their own performance and their returns to effort. Similar diverging results were found in a Mexican study that provided disadvantaged students with feedback on their performance on a mock version of an admission test before they had to apply for secondary schools and take the real test (Bobba & Frisancho, 2016). The study found that feedback information substantially reduced the gap between perceived and actual performance and that students who updated their beliefs upward responded to the new information by applying for and enrolling in more academically oriented secondary schools.…”
Section: Information About Behaviour and Abilitysupporting
confidence: 62%
See 1 more Smart Citation
“…We note that the largest effects were among new students who were likely to be less informed about their own performance and their returns to effort. Similar diverging results were found in a Mexican study that provided disadvantaged students with feedback on their performance on a mock version of an admission test before they had to apply for secondary schools and take the real test (Bobba & Frisancho, 2016). The study found that feedback information substantially reduced the gap between perceived and actual performance and that students who updated their beliefs upward responded to the new information by applying for and enrolling in more academically oriented secondary schools.…”
Section: Information About Behaviour and Abilitysupporting
confidence: 62%
“…A common feature of the interventions in Pistolesi (2017), Bandiera et al (2015) and Bobba & Frisancho (2016) is that they provide personalised information which may potentially de-bias beliefs about own ability or effort level, and therefore induce individuals to reoptimise behaviour (e.g. effort choices) and pathway (e.g.…”
Section: Mt Damgaard Hs Nielsen Economics Of Education Review 64mentioning
confidence: 99%
“…Another source of inequity that provides a rationale for government intervention are information constraints. Individuals often lack accurate information about the costs of acquiring skills or about the benefits of investing in skills (Dinkelman and Martínez, 2014;Bobba and Frisancho, 2016;Jensen, 2010;Hastings et al, 2016). There are many examples of these information failures.…”
Section: %mentioning
confidence: 99%
“…The goal 7 See http://diplomasnow.org/our-impact/. 8 For recent examples, see Bobba and Frisancho (2016), Dinkelman and Martínez (2014), Avitabile and de Hoyos (2015), and Jensen (2010). 9 Early results show that the program promoted socioeconomic diversity in elite universities.…”
Section: But It Takes More Than Moneymentioning
confidence: 99%
“…In the same context under study in this paper, Bobba and Frisancho [2014] focus on the role of students' self-perceptions about academic ability as a potential source of distortion for perceived track-specific returns and hence high school choice decisions, while De Janvry et al [2013] highlights the potential trade-off between drop-out risk and academic benefit behind students' demand for "elite" public high schools.…”
Section: Introductionmentioning
confidence: 99%